The Growing Power Struggle in Indian Ocean Region: Security Road Map for Bangladesh - Krishnan, Tharishini; Mahmud Safeer, Abu Sadat; Singh, Inderjit (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
The Indian Ocean Region (IOR) is rising significantly as the center stage for world politics in the current century. Due to the geostrategic and economic importance, the region has created conflicts in strategic interest leading to power confrontation among regional and extra-regional powers resulting in security threats for small littorals like Bangladesh. Some of the threats are influential attachments of the powerful states in foreign, trade, economy and defense sectors, poor regional security architecture and an increase of non-traditional security threats. Analyzing the issues reveals that, Bangladesh can navigate these challenges by playing strategic hedging, pursuing multilateralism, recalibrating trade and economic engagements, and comprehensive drive by government agencies to deal with non-traditional security threats.